Clinical application of a ventilation strategy based on the P-V curve in obese patients undergoing gynaecological laparoscopic surgery - Zhixia Zhou; Fei, Guofang; Zhang, Qi; Ru, Yi (Journal of the Pakistan Medical Association, 2025)
Objective: To explore the clinical value of pressure-controlled ventilation-volume guaranteed (PCV-VG) strategy based on the pressure-volume curve method in obese patients undergoing gynaecological laparoscopic surgery. Method: The retrospective study was conducted in December 2021 after approval from the ethics review committee of Huzhou Maternal and Child Health Hospital, China, and comprised clinical records of obese patients who underwent elective gynaecological laparoscopic surgery between January 2020 and October 2021. The patients were divided into study group A, who underwent surgery with PCV-VG, and control group B, who underwent surgery without the PCV-VG. Ventilation parameters in group A were individually set according to the pre-pneumoperitoneum pressure-volume curves. Respiratory parameters, peak airway pressure, end-tidal carbon dioxide partial pressure, mean arterial pressure and patients' postoperative comfort scores were compared between the groups after tracheal intubation, pneumoperitoneum, and postural positioning. Data was analysed using SPSS 22. Results: Of the 200 patients, 40(20%) were cases of laparoscopy myomectomy, 152(76%) cases of ovarian cystectomy, and 8(4%) cases of hysterectomy. There were 100(50%) females in group A with a mean age of 43.15±4.24 years, and 100(50%) were in group B with a mean age of 42.69±4.01 years (p=0.12). The peak airway pressure, mean arterial pressure, pneumoperitoneum pressure, and head-down tilt of the patients in group A were significantly lower post-pneumoperitoneum and post-positioning (p<0.05). At the same time, the respiratory rate was considerably higher (p<0.05) than that in group B. The end-tidal carbon dioxide partial pressure value at all time points was not significantly different between the groups (p>0.05). Postoperative comfort scores of patients in group A were significantly higher than those of group B (p<0.05). Conclusion: PCV-VG, based on the pressure-volume curve, significantly reduced intraoperative peak airway pressure, was associated with smoother hemodynamic, and regulated intraoperative pneumoperitoneal pressure and position in obese patients undergoing gynaecological laparoscopic surgery. The ventilation method also significantly improved the patients' postoperative comfort. Key Words: P-V curve, PCV-VG, Obese, Posture, Pneumoperitoneum pressure, Laparoscopy.